A Biomechanical Analysis of the Modified Taekwondo Axe Kick - Bercades, Luigi T.; Pieter, Willy (Revista de Artes Marciales Asiáticas, 2012)
This study is a theoretical analysis of the kinematic and kinetic aspects of the modified taekwondo axe kick. The traditional or classical axe kick has the whole kicking leg (the thigh and the shank) considered as a rigid body on both the upswing and downswing phases of the kick, which is speculated to have sufficient angular momentum to increase the risk of some forms of injuries in competition. The present study seeks to present an alternate version that will decrease the moment of inertia on the downswing, reduce the subsequent angular momentum, and finally decrease the resultant impulse to the target. Theoretically, this will reduce the chances of certain types of injury caused by the kick.